The Effect of Virtuous and Entrepreneurial Orientations on Microfinance Lending and Repayment: A Signaling Theory Perspective - Moss, Todd W.; Neubaum, Donald O.; Meyskens, Moriah (Entrepreneurship Theory and Practice, 2015)
The availability of capital for microenterprises has grown rapidly due to microfinancing platforms such as Kiva. The investment decisions of microlenders are challenged due to the limited information about the microenterprises’ characteristics and behavioral intentions. Extending signaling theory, we suggest that microenterprises’ narratives on microfinancing platforms are an important means to signal valuable characteristics and behavioral intentions to prospective lenders. Results indicate that microenterprises, which signal autonomy, competitive aggressiveness, and risk–taking, are more likely to receive funding, and to receive it more quickly. Microenterprises that signal conscientiousness, courage, empathy, and warmth are less likely to get funded. Rhetorical signaling proactiveness, conscientiousness, courage, warmth, or zeal is negatively associated with loan repayment.